Sustainability Potential and Utilization of Agricultural Bioenergy in Turkey - Dursun Kemal Bayraktar (BioResources)
Over the past decade, advances in bioenergy technology have enabled the expansion of renewable energy consumption. Projections indicate that roughly 30% of the anticipated increase in renewable energy utilization will stem from modern bioenergy in its solid, liquid, and gaseous fuel manifestations, owing to its substantial role in heat and transportation sectors. At present, fossil fuels account for 60% of global electricity generation, while renewables contribute 30%. Notably, Turkey surpasses this global average, with renewables constituting 36% of its electricity production. In 2002, Turkey’s electricity output from renewable sources stood at 34 billion kWh; by 2023, it had surged by 300% to reach 200 billion kWh. Likewise, the installed renewable energy capacity, which was about 12,300 MW in 2002, has more than tripled, exceeding 82,700 MW in 2023. This research delves into biomass, a key pillar of renewable energy, analyzing its potential, technological advancements, significance, and current status in Turkey. Furthermore, it aligns with one of Turkey’s foremost energy strategies that focuses on enhancing domestic and renewable energy production.